QUALITY ANALYSIS OF SUPPORT MARKETING AND QUALITY OF SALES TRAINING ON SALES PERFORMANCE CAPABILITY ON PERFORMANCE SALES PERFORMANCE - Hapsari, Ria Mawar; Indriani, Farida; Sutopo, Sutopo (Master of Management Diponegoro University, 2017)
This study aims to analyze and examine the effect of quality marketing support, sales quality, sales force capability to salespeople performance, with the formulation of the problem of